Impact of Growth Opportunities, FinTech, and Intellectual Capital on Banking Stability: The Mediating Role of Financial Performance - Daniela Setiani Hutajulu; Rike Setiawati; Besse Wediawati (Universitas Darwan Ali, 2026)
The importance of banking stability as a pillar of national economic resilience cannot be overstated, as any disruption in this sector risks creating systemic impacts on the country's economy. Against this backdrop, this study was conducted to analyze the influence of growth opportunities, financial technology, and intellectual capital on banking stability, positioning financial performance as an intervening variable. The study gathered data from the annual financial reports of 32 banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Data processing was performed using descriptive statistics and structural equation modeling via the Partial Least Squares (SEM-PLS) method. Based on the analysis, it was found that growth opportunities, financial technology, and intellectual capital each have a positive and significant impact on financial performance. Furthermore, the results demonstrate that growth opportunities, financial technology, intellectual capital, and financial performance directly exert a positive and significant influence on banking stability. These findings also confirm the role of financial performance as a successful mediator in the relationship between growth opportunities, financial technology, intellectual capital, and banking stability. Overall, these results emphasize that enhancing financial performance is a primary strategic pathway for strengthening the stability of the banking sector in Indonesia.